BUDIDAYA TANAMAN PINANG (ARECA CATECHU L ) SPESIFIK TEKNIK PEMBIBITAN DI DESA OMBOLATA KECAMATAN AFULU - Nonozisokhi Gea; Karunia Gea (Haga : Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service activity is to provide understanding and awareness for the people of Ombolata Afulu Village, Afulu District, that what planting media is suitable for use in betel nut nurseries. The method used in this service is the lecture method in the form of outreach used with participants consisting of areca nut farming communities in Ombolata Afulu Village, Afulu District. This activity was carried out at the Bobotalu Afulu ONKP Church on Friday, May 5 2023. The results obtained from this dedication were the people of Ombolata Afulu Village, Afulu District. Socialization activities regarding the cultivation of areca plants (seeding techniques) have been carried out well, in the cultivation of areca plants various factors are very decisive. One of the most important factors is the success of the areca plant nursery process. This needs to be considered because the areca plant also requires a relatively longer time in the germination process, so a planting medium that is really suitable is needed. The conclusion from this community service activity is that the nursery is carried out using planting media derived from tofu dregs and the germination process of areca seeds is best done in the dark.